Disability, employment and stress regarding ability to pay for housing and healthy food. - Smith, Diane L. (Work, 2013)
OBJECTIVE: To determine if disability is a significant factor in increasing the likelihood of experiencing stress regarding the ability to pay for housing and healthy food. PARTICIPANTS: 24.6% (n=16206) of 65,960 adults who responded to the social context optional module of 2009-2010 Behavioral Risk Factor Surveillance System identified themselves as having a disability. Adults with disabilities reported that they experienced significantly more stress about having money to pay for housing and healthy food than adults without disabilities. METHODS: This research was a quantitative study using a publicly available dataset. A series of logistic regressions were performed to determine the extent that disability affected the likelihood of stress about having enough money for housing and healthy food.RESULTS: Employed persons with a disability are 1.6 times and 1.9 times as likely as persons without a disability to experience stress about not having enough money to pay for housing and healthy food, respectively. Persons not employed with a disability are 1.56 times and 1.83 times as likely to experience stress about not having enough money to pay for housing and healthy food, respectively. For persons with a disability, being female, in poor health, without a health plan and having a lower income were also significant. Education and employment were not significant predictors of experiencing stress regarding money for food or housing. CONCLUSIONS: Having a disability is more predictive of experiencing stress about having enough money for housing and healthy food than employment, though variables such as low income and having a health plan, dependent on employment are significant. Therefore, strategies and policy recommendations to reduce stress by increasing employment and income for persons with disabilities were presented.